Evaluation of awareness and importance of child vaccination among mothers carrying children of age 1 to 4 years in Lyari, Karachi, Pakistan - Siddiqui, Nausheen Hameed; Yousaf, Shanza; Saeed, Javaria; Wahid , Shahana; Abdul Khaliq, Sheikh; Ahmed, Imran (International Journal of Pathology, 2026)
Background: Despite attempts to promote immunization, Pakistan's suboptimal child vaccination rates lead to avoidable diseases and high infant mortality, demanding a better understanding of mothers' vaccination knowledge. The current study aimed to assess the level of awareness and knowledge regarding childhood vaccination among mothers and examine its association with demographic characteristics.Methods: A cross-sectional survey was conducted among 250 mothers using a structured validated questionnaire. The data collected included demographic information, knowledge of vaccine benefits, and perceptions of vaccination schedules. The association between awareness and chosen factors were evaluated statistically using Chi-square.Results: The 67.2% respondents, demonstrated awareness about vaccination. Significant associations were observed between vaccination awareness and educational level (p=0.0001), number of children (p=0.004), and age of the youngest child (p=0.002). Mothers who acknowledged the benefits of vaccination and the role of vaccines in preventing diseases were significantly more likely to have vaccinated their children (p<0.001). However, gaps remained in knowledge related to vaccine schedules, misconceptions about vaccination during illness, and the belief that one vaccine can immunize against all diseases.Conclusion: Our findings emphasize the necessity for targeted health education programs to upgrade maternal knowledge and correct misconceptions about childhood immunization. Community-based interventions including healthcare professionals, media, and local influencers are advised to increase vaccine uptake and achieve complete vaccination coverage. ‎